2009
DOI: 10.1089/ars.2009.2614
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Mitochondrial Clusters Containing Mutant SOD1 in Transgenic Models of ALS

Abstract: We studied the subcellular distribution of mitochondria and superoxide dismutase-1 (SOD1) in whole mounts of microdissected motor axons of rats expressing the ALS-linked SOD1-G93A mutation. The rationale was to determine whether physical interactions between the enzyme and mitochondria were linked to the axonopathy of motor fibers occurring in amyotrophic lateral sclerosis (ALS). Mitochondria and SOD1 displayed a homogeneous distribution along motor axons both in nontransgenic rats and in those overexpressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…In addition, dense conglomerates of mitochondria in the anterior horn of lumbar spinal cord and proximal axons have been found in sporadic ALS patients [43,44]. Abnormal clustering of mitochondria was recently reported in motor axons in mutant SOD1 transgenic mice [45]. Extensive fragmentation of mitochondria was also reported in cultured NSC34 cells overexpressing mutant SOD1 [46,47].…”
Section: Abnormal Mitochondrial Morphology and Bioenergetics In Alsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, dense conglomerates of mitochondria in the anterior horn of lumbar spinal cord and proximal axons have been found in sporadic ALS patients [43,44]. Abnormal clustering of mitochondria was recently reported in motor axons in mutant SOD1 transgenic mice [45]. Extensive fragmentation of mitochondria was also reported in cultured NSC34 cells overexpressing mutant SOD1 [46,47].…”
Section: Abnormal Mitochondrial Morphology and Bioenergetics In Alsmentioning
confidence: 91%
“…Abnormal mitochondrial clustering and fragmentation [43,44,46,47,131] and altered mitochondrial transport [115,117,132] are highly suggestive that mitochondrial dynamics may be influenced in the presence of mutant SOD1. A recent study showed mitochondrial fragmentation, impaired mitochondrial dynamics, and decreased density of mitochondria along neurites in differentiated NSC34 cells expressing mutant SOD1 [117].…”
Section: S317mentioning
confidence: 99%
“…A number of potential scenarios exist. Of particular interest is the observation that mutant SOD1 preferentially accumulates at the cytoplasmic face of the outer membrane and in the intermembrane space of mitochondria (Cozzolino et al 2009;Ferri et al 2006;Higgins et al 2003;Sotelo-Silveira et al 2009). Therefore, it is possible that an aberrant association between mutant SOD1 and mitochondrial proteins may lead to impaired electron transport chain functioning, shortage of ATP, increased ROS formation and Ca 2+ dysregulation.…”
Section: Mitochondrial Morphological Abnormalities and Dysfunctions Imentioning
confidence: 99%
“…These trafficking abnormalities along with the observations of mitochondrial fragmentation and axonal clustering [188,189] are highly suggestive that mitochondrial dynamics modulated by mutSOD1 may play a critical role in ALS pathogenesis. However, as mutSOD1 only account for 3% of ALS cases the mitochondrial role in the pathogenesis of most common sporadic form of ALS has to be yet proved.…”
mentioning
confidence: 78%